Female condom for preventing HIV and sexually transmitted infections - Bame, Ruth (Cochrane Database Syst Rev, 2018)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: 1. To determine the effectiveness of the female condom in preventing HIV; and 2. To determine the effectiveness of the female condom in preventing STIs.